ANALISA RISIKO PEKERJAAN REHABILITASI JARINGAN IRIGASI DI.WARU KABUPATEN PENAJAM PASER UTARA PROVINSI KALIMANTAN TIMUR - ALI, AKHIRUDDIN (KURVA S JURNAL MAHASISWA, 2018)
The risk is one of the things that can not be separated in daily live as well as the implementation of construkctions projeck did not separated with the risk. Irrigation canal is the unity of the cannals and the building which needed for the irrigation water settings, that starting from provision, water taking, division,water giving and water using of the problem the research with tittle â€œthe risk analysis of rehabilitation of canals irrigation construction in DI. Waru panajam pasir utara district, east Borneoâ€ Construction and what are how to identify the risk of rehabilitation the most influenced to the rehabilitation construction. The purpose of this study was to identifyed the risk in the rehabilitation construction and to analysied the risk that gives the most negative effect while the rehabilitation construction. Method of this study was quantitative and the souses of this study was quitioner and interview. The data would be analysed by peartson product moment and probability impact matrix method, and likert scale was the theoritical basis of this study. Based on data analysis, the research found that from 27 variables there was 23 variables was valid and 4 variable was not valid. the presentation from 4 variables that have high category was 17.5%.